Clinical profile and antibiotic sensitivity pattern of typhoid fever in children: a hospital based prospective study from a tertiary care center - V., Shekar; Soren, Chapay; V. V., Lakshmi Aparnadevi; M., Umadevi; Vanka, Malathi (International Journal of Contemporary Pediatrics, 2020)
Background: Typhoid fever is a serious public-health problem in many developing countries including India. There is a wide spectrum of clinical presentation and with the emergence of multidrug resistant typhoid now a days, the treatment has become still more complex. The present study authors describe the clinical profile and antibiotic sensitivity pattern of typhoid fever in children from a tertiary care in Mahabubnagar, Telangana, South India. Methods: This hospital based prospective observational study was done in Department of Pediatrics, SVS Medical College, Mahabubnagar, Telangana over a period of 3-year period from January 2017 to December 2019. The study was approved by institutional ethics committee. Written informed consent was obtained from children’s parents. All pediatric patients diagnosed as typhoid fever if presented with fever (temperature >38ºC) for at least 3 days with positive blood culture for S. typhi or paratyphi were included in the study. The demographic profile and clinical data were recorded and tests including antibiotic sensitivity and resistance were done. Results: A total of 136 patients were included in the study. Majority of the children were between 8 to 12-year age group (38.2%). Out of 136 children, 78 were males and 58 were females. Majority of the cases were from rural areas accounting for 69%. Drinking water source was tap water in 63% cases and bore well water in 37% cases. Majority (65%) belonged to lower socioeconomic class and 68% were during rainy seasons. The clinical findings observed were fever (100%), vomiting (98, 72%), diarrhea (55.8%), headache (45.5%), and splenomegaly (42.6%). Other clinical features found were coated tongue, abdominal pain, hepatomegaly, constipation, and dehydration. Six children had complications, 3 had enteric hepatitis, 2 had shock, and 1 had encephalopathy. Ampicillin, amoxicillin and chloramphenicol resistance was observed in 76%, 71% and 22% of patients with typhoid fever respectively. Maximum sensitivity was observed with ceftriaxone (95%), followed by aztreonam (92%), ciprofloxacin (84.5%), and azithromycin (77%). Conclusions: Clinical presentation in the study subjects was similar to available reports from literature. Increasing resistance of salmonella to Ampicillin and amoxicillin were observed.